Epidemiological evaluation of apical periodontitis prevalence in an urban Brazilian population - Teresa BERLINCK; Justine Monteiro Monnerat TINOCO; Fernanda Leal Fonseca CARVALHO; Luciana Moura SASSONE; Eduardo Muniz Barretto TINOCO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The present study aimed to assess the prevalence of apical periodontitis (AP) in an urban Brazilian population according to gender, age group and tooth type. Data were collected from clinical files containing the medical and dental histories and periapical radiographs of 1,126 patients treated at the School of Dentistry at Universidade do Estado do Rio de Janeiro between March 2000 and December 2010. A total of 15,724 periapical radiographs were evaluated. All the radiographs were evaluated by two independent, previously calibrated endodontists (kappa = 0.88). Periapical areas on the radiographs were classified as N (normal) or AR (apical radiolucency). The frequency of AP and the 95% Confidence Interval (95%CI) were calculated according to gender, age group and tooth type. Differences between groups were calculated using the Z-test at a significance level of 5% (p < 0.05). AP was present in 7.87% of the samples, with 16.70% occurring on previously endodontically treated teeth and 44.65% occurring on teeth referred for endodontic treatment (TR-RCT). The frequency of AP was higher among females (64%) than among males (35%). The central and lateral maxillary incisors were the most frequently affected teeth. The frequency of AP was higher among individuals between 30 and 49 years of age. In this population, AP was more prevalent among females and among individuals between 30 and 49 years of age, and the central and lateral maxillary incisors were the most frequently affected teeth.